Analysis of performance and gene OsFER1 expression of six rice varieties with FeSO4 stress treatment - FAUZIAH KHAIRATUNNISA; ANDI SALAMAH; ANDI EKO MARYANTO (Society for Indonesian Biodiversity, 2023)
Abstract. Khairatunnisa F, Salamah A, Maryanto AE. 2023. Analysis of performance and gene OsFER1 expression of six rice varieties with FeSO4 stress treatment. Biodiversitas 24: 1391-1399. Efforts to meet rice needs in Indonesia can be made through an extensification program. New paddy fields generally have a high FeSO4 content, so rice varieties resistant to these conditions are needed. This study aims to evaluate the growth of lowland rice varieties under FeSO4 stress and to analyze the expression of a gene that plays a role in iron storage, namely the OsFER1. Six lowland rice varieties, namely Ciherang, Inpari 42, Inpari 30, Sunggal, Logawa, and Cibogo were grown on media with 0 and 400 ppm FeSO4 applications. The plant height, leaf bronzing score, and the number of filled grains produced were observed to determine the effect of FeSO4 administration on the agronomic performance of rice. The OsFER1 gene expression ratio was analyzed using real-time PCR. The best plant height at 400 ppm FeSO4 was found in the Inpari 30 variety (40.3 ± 0.49 cm), with a leaf bronzing score was 1. The Inpari 30 also produced grain at 400 ppm FeSO4. Molecular analysis showed that the highest OsFER1 expression was found in the Inpari 30 grown at 400 ppm FeSO4. Based on morphological and molecular observations, Inpari 30 is tolerant to FeSO4 stress.